Mediated forensics and militant evidence: rethinking the camera as weapon. (January 2023) - Smith, Patrick Brian; Watson, Ryan
This article focuses on new media technologies and practices that are reshaping how human rights media activism is practiced, disseminated and received. Through an examination of two works by the research agency Forensic Architecture, we examine how these new technologies and practices aim to reframe and deploy forms of raw media evidence in human rights struggles and broader modes of political activism. We also consider how these nascent forms of activist media practice are indebted to the broader legacies of radical documentary practice, particularly through the theoretical lineage of the "camera as weapon." The new technological and aesthetic strategies being developed and utilized by these groups are radically reshaping investigatory methodologies and collaborative practices across contemporary human rights, documentary, and new media practice. Ultimately, within these new ecologies of media practice, raw forms of media evidence are reframed and redeployed; entering into larger assemblages and ecologies to examine – and concomitantly resist – formations of political power and state violence. This is a practice that we term "mediated forensics."